ANALISIS NILAI-NILAI KARAKTER BANGSA DI DALAM BUKU TEKS PELAJARAN SEJARAH WAJIB SMA KELAS X - Bilowo Setya Nugraha; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The problem in this study refers to the value of national character contained in each compulsory history textbook for grade X high school students. The teacher has not conveyed the values of national character optimally. In addition, the history learning textbook does not include the values of the national character in complete and detail. The research objectives related to the problem can be put forward, among others, to analyze the application of character values in the history learning curriculum syllabus for grade X SMA, analyze the identity and content of the history learning textbook for class X high school, analyze what character values are contained in the Compulsory High School History Textbook.class X and analyzed the character values contained in each textbook material of history compulsory high school class X. This study used a qualitative research method. Researchers also used a descriptive analysis approach, namely by analyzing, describing the contents or problems being studied. The results of the study regarding the analysis of the national character values contained in thecompulsory history textbook for grade X SMA, the researcher found that many character values contained in the Indonesian History book for SMA / MA class X and have not been included in full in this book. The researcher presents the national character values along with the materials that contain these character values.